Trade Must Go On. The Tar Trade, Nordic Rivalry, and Cross-Imperial Commercial Diplomacy, 1675–79 - Wirta, Kaarle; Hannula, Henri (Legatio: The Journal for Renaissance and Early Modern Diplomatic Studies, 2022)
The Scanian War fought between Sweden and Denmark (1675–1679) is an example of an armed conflict, which uncovers the clash between the commercial and political interests. This article analyses the dispute between the political allies, the Danish Crown and the Dutch States General considering the trade with Sweden. The Danish naval officials had captured and confiscated the cargoes of seven Dutch tar vessels, heading to Amsterdam from present-day Finland in 1677, which resulted in a major political dispute between Denmark and the Dutch Republic. By drawing upon the methodology of new diplomatic history, the article analyses the negotiations between the diplomatic actors involved in the disputes relating to the confiscation of the ships, all of whom represented the various powers involved in the Baltic export trade.